Community-Based Waste Management in Tabalong Regency - Muhammad Noor Ifansyah; Purwanto Purwanto; Hartuti Purnaweni; Tri Yuniningsih; Ahmad Anwar (Universitas Teuku Umar, 2023)
One of the global challenges is the increasing amount of waste generation. In Indonesia, there is an average increase in waste of around 7.02% after a year. Efforts to reduce waste generation are a very important issue. The impact of waste generation can reduce environmental quality and even have a bad impact on health. The Tabalong Regency Government is one of the districts that seek to overcome the waste problem, changing the paradigm of waste management by issuing local regulations regarding waste management is a step that is trying to be implemented. The research was conducted in Tabalong Regency, South Kalimantan Province, using a descriptive qualitative approach and to analyze the phenomena that occurred then analyze them using an interactive model to find an analysis of community-based waste management in Tabalong Regency. The research was conducted by interviewing the Head of the Tabalong Environmental Service with a dissertation of supporting documents accessed through the National Waste Management System page. Based on the results of the study, it was found that the Tabalong Regency government has committed to waste management to support national waste management policies to reduce waste generation. The commitment of the Tabalong Regency Government is contained in Regional Regulation Number 14 of 2017 concerning Waste Management with an emphasis on community participation as an effort to reduce waste from the source. The Waste Bank and TPS 3R programs involve community participation in waste management.